2022
DOI: 10.1038/s41419-022-05315-5
|View full text |Cite
|
Sign up to set email alerts
|

c-Mpl-del, a c-Mpl alternative splicing isoform, promotes AMKL progression and chemoresistance

Abstract: Acute megakaryocytic leukemia (AMKL) is a clinically heterogeneous subtype of acute myeloid leukemia characterized by unrestricted megakaryoblast proliferation and poor prognosis. Thrombopoietin receptor c-Mpl is a primary regulator of megakaryopoeisis and a potent mitogenic receptor. Aberrant c-Mpl signaling has been implicated in a myriad of myeloid proliferative disorders, some of which can lead to AMKL, however, the role of c-Mpl in AMKL progression remains largely unexplored. Here, we identified increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Genes exhibiting higher levels of AS tend to engage in more protein-protein interactions, thereby contributing to increased protein diversity. Additionally, splicing dysregulation can lead to isoform switching in oncogenes, enabling cancer cells to develop resistance to anticancer therapies [ 54 ]. In our study, we observed that the knockdown of EIF3D lead to alterations in various types of ASEs in FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…Genes exhibiting higher levels of AS tend to engage in more protein-protein interactions, thereby contributing to increased protein diversity. Additionally, splicing dysregulation can lead to isoform switching in oncogenes, enabling cancer cells to develop resistance to anticancer therapies [ 54 ]. In our study, we observed that the knockdown of EIF3D lead to alterations in various types of ASEs in FaDu cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the deletion or gene knockout of NOVA2 can prevent the normal formation of the vascular lumen. 24 38 The progression of LF is often accompanied by vascular proliferation, which promotes the activation and proliferation of HSC by furthering the transport of oxygen and nutrients, thus promoting the progress of LF. 29 32 The point is whether NOVA2 plays a key role in LF.…”
Section: Discussionmentioning
confidence: 99%
“…AEL is a rare subtype of AML characterized by prominent erythroid proliferation [22]. AMKL is characterized by the unrestricted proliferation of immature megakaryocytes (megakaryoblasts) and extensive myelofibrosis [23]. In addition to these subtypes, AML can be further classified based on specific genetic abnormalities.…”
Section: Subtypes Of Acute Leukemia and Their Characteristicsmentioning
confidence: 99%